Cluster‐Bridging‐Coordinated Bimetallic Metal−Organic Framework as High‐Performance Anode Material for Lithium‐Ion Storage. Issue 12 (29th October 2021) - Yan, Wen; Fan, Kun; Zheng, Li-Min; Jin, Zhong
Abstract : Metal−organic frameworks (MOFs) are potential electrode materials for energy storage owing to abundance of active sites, structural versatility, and well‐organized porous framework. Herein, a cluster‐bridging‐coordinated bimetallic Co4 (μ4 ‐O)[Ir(ppy‐COO)3 ]2 MOF (Co4 ‐Ir MOF) with high conductivity and desirable porosity is proposed as promising anode materials for Li + storage. The Co4 ‐Ir MOF consists of Co4 (μ4 ‐O) clusters bridge‐coordinated by Ir(ppy‐COOH)3, leading to electrical conductivity four orders of magnitude higher than that of conventional insulating MOFs and Li + diffusion coefficient two orders of magnitude higher than that of graphite, thus boosting rate capability. The laminated stacking structure and ordered porous framework of Co4 ‐Ir MOF ensure rapid Li + transport and storage without large volume variation. As a result, Co4 ‐Ir MOF anodes deliver high capacity of 1202 mAh g −1, outstanding rate performance (515 mAh g −1 at 3000 mA g −1 ), and good cycling stability (average capacity decay of 0.041% per cycle for 1000 cycles). Soft‐packed full batteries assembled with Co4 ‐Ir MOF anodes and LiNi0.5 Co0.2 Mn0.3 O2 cathodes exhibit good stability and flexibility. Moreover, Co4 ‐Ir MOF anode with fast kinetics is applied in hybrid lithium‐ion capacitor, demonstrating good compatibility with capacitor‐type cathode. This work suggests great potential to rationally design MOF materials with intriguing structures and performances for sustainable energy storage applications. Abstract : A cluster‐bridging‐coordinated bimetallic Co4 ‐Ir MOF consisting of [Ir(ppy‐COOH)3 ] metallolinkers and cobalt ion (II) nodes is proposed as a promising anode material for lithium ion storage. The bimetallic cluster‐bridging‐coordinated Co4 ‐Ir MOF with laminated stacking structure and ordered porous framework exhibits significantly higher electrical conductivity and superior ion transport properties than those of conventional MOFs, thus significantly improving the electrochemical performance.